2019
DOI: 10.1371/journal.pone.0208871
|View full text |Cite
|
Sign up to set email alerts
|

Selection of trait-specific markers and multi-environment models improve genomic predictive ability in rice

Abstract: Developing high yielding rice varieties that are tolerant to drought stress is crucial for the sustainable livelihood of rice farmers in rainfed rice cropping ecosystems. Genomic selection (GS) promises to be an effective breeding option for these complex traits. We evaluated the effectiveness of two rather new options in the implementation of GS: trait and environment-specific marker selection and the use of multi-environment prediction models. A reference population of 280 rainfed lowland accessions endowed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 64 publications
3
29
1
Order By: Relevance
“…to 32%. Similar gains of PA were reported in dairy cattle for milk yield and in rice for traits related to drought tolerance (Bhandari et al 2019). Using GRM built with markers identified through GWAS in Holstein-Friesian bulls, Veerkamp et al (2016) reported no increase in the accuracy of genomic predictions compared to GRM built with a large set of markers including or not trait-specific SNPs.…”
Section: Marker Density and Use Of Trait-specific Markerssupporting
confidence: 56%
See 3 more Smart Citations
“…to 32%. Similar gains of PA were reported in dairy cattle for milk yield and in rice for traits related to drought tolerance (Bhandari et al 2019). Using GRM built with markers identified through GWAS in Holstein-Friesian bulls, Veerkamp et al (2016) reported no increase in the accuracy of genomic predictions compared to GRM built with a large set of markers including or not trait-specific SNPs.…”
Section: Marker Density and Use Of Trait-specific Markerssupporting
confidence: 56%
“…Hassen et al (2017), using DTF and GY data from two managed environments (AWD and CF), reported PA gains of up to 30% by using multi-environment models compared to their single-environment counterparts. Likewise, Bhandari et al (2019) using rice DTF and GY data from three managed drought experiments, reported PA gains of up to 32% with the RKHS multi-environment models. In the present study, the two multi-environment models (GBLUP and RKHS) provided similar substantial gains of PA, despite the fact that under the M×E model implemented with GBLUP, the environmental covariance is forced to be positive and constant across pairs of environments.…”
Section: Accounting For G × E Interactions and For Correlation Betweementioning
confidence: 98%
See 2 more Smart Citations
“…Robustness is measured by comparing the mean phenotype between two environments or by measuring the variance of the phenotype between two environments [28]. A rst approach involves building a model based on large-scale multi-environment phenotyping in order to quantify Genome x Environment effects [29,30]. However, the disadvantage of this approach arises from di culties in nding reliable models that correlate traits and their environment drivers [29].…”
Section: Introductionmentioning
confidence: 99%